Interpreter of Maladies - Lahiri, Jhumpa (Faridabad: HarperCollins, 2019)
Navigating between the Indian traditions they've inherited and the baffling new world, the characters in Jhumpa Lahiri's elegant, touching stories seek love beyond the barriers of culture and generations. In "A Temporary Matter," published in The New Yorker, a young Indian-American couple faces the heartbreak of a stillborn birth while their Boston neighborhood copes with a nightly blackout. In the title story, an interpreter guides an American family through the India of their ancestors and hears an astonishing confession. Lahiri writes with deft cultural insight reminiscent of Anita Desai and a nuanced depth that recalls Mavis Gallant.
Keywords: East Indians- Fiction -- Immigrants -- United States; Families -- Cultural assimilation -- India